Leiomyoma of the breast: a case report - Nazário, Afonso Celso Pinto; Tanaka, Carlos Itio; Lima, Geraldo Rodrigues de; Gebrim, Luiz Henrique; Kemp, Cláudio (São Paulo Medical Journal, 1995)
A rare case of leiomyoma of the breast is reported, with a discussion of the clinical aspects and of the differential diagnosis. Excluding tumors originating from the areolar-papillary complex and the skin, this neoplasm is extremely rare, with only 11 cases reported so far. The histogenesis of the lesion is still controversial.